Detailed characterisation of invasive aspergillosis in a murine model of X-linked chronic granulomatous disease shows new insights in infections caused by Aspergillus fumigatus versus Aspergillus nidulans - King, Jill; Dambuza, Ivy M.; Reid, Delyth M.; Yuecel, Raif; Brown, Gordon D.; Warris, Adilia (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Invasive aspergillosis (IA) is the most prevalent infectious complication in patients with chronic granulomatous disease (CGD). Yet, understanding of fungal pathogenesis in the CGD host remains limited, particularly with regards to A. nidulans infection. Methods We have used a murine model of X-linked CGD to investigate how the pathogenesis of IA varies between A. fumigatus and A. nidulans, comparing infection in both X-linked CGD (gp91 -/-) mice and their parent C57BL/6 (WT) mice. A 14-colour flow cytometry panel was used to assess the cell dynamics over the course of infection, with parallel assessment of pulmonary cytokine production and lung histology. Results We observed a lack of association between pulmonary pathology and infection outcome in gp91 -/- mice, with no significant mortality in A. nidulans infected mice. An overwhelming and persistent neutrophil recruitment and IL-1 release in gp91 -/-mice following both A. fumigatus and A. nidulans infection was observed, with divergent macrophage, dendritic cell and eosinophil responses and distinct cytokine profiles between the two infections.We have provided an in-depth characterisation of the immune response to pulmonary aspergillosis in an X-linked CGD murine model. This provides the first description of distinct pulmonary inflammatory environments in A. fumigatus and A. nidulans infection in X-linked CGD and identifies several new avenues for further research.